Blood rheology and proliferative retinopathy in sickle cell-haemoglobin C disease. Issue 5 (May 1984) - Serjeant, B E; Mason, K P; Condon, P I; Hayes, R J; Kenny, M W; Stuart, J; Serjeant, G R
Abstract : Haematological and rheological (plasma and serum viscosity, whole blood viscosity, and erythrocyte filterability) factors were studied in 31 age-sex matched pairs of patients with sickle cell haemoglobin C disease with and without proliferative sickle retinopathy (PSR). Patients with PSR had significantly higher mean cell haemoglobin and lower Hb F levels on average than the matched controls, but the viscosity and erythrocyte filtration indices did not differ between the 2 groups. There was, therefore, no evidence of rheological differences between patients with and without PSR at the time of the study, although transient rheological abnormalities at the time of development of PSR could not be excluded. Prospective longitudinal studies of rheology before, during, and after the development of PSR would be necessary to detect such changes.